Flux analysis and it’s influence on drops mean diameter for Y type internal mixture injectors - Quispe Gonzáles, C. A. (2012)
The Y type injectors are classified as internal mixture injectors and are very useful in industries.The calculation methods are based on the sonic flux conditions to enter to mixture chamber. Inthis work, we present a calculation method for these injectors in the subsonic regime where theoperation conditions such as the injector geometry, the pressure and temperature conditions,the properties and mass spend of gaseous and liquid fuel of atomization are known. Underthese conditions, an analysis of Wigg equation -which determine the drops mean diameter-,show that, in the critic regime only permit us to obtain the lesser spray drops mean diameter.For any other condition, the atomization gas flows under a subsonic regime and the drop meandiameter is greater that the minimum value. Also, we compare between different equationswhich define the drop mean diameter in differents variants of Wigg equations, propossed indifferent published woks, which obtain different results, this is due to a wrong interpretationof the physical essence of the Wigg equation.